Alex Cross's trial a novel - Patterson, James 1947-; DiLallo, Richard (New York Little, Brown, 2009)
Detective Alex Cross tells the story of an ancestor, Abraham Cross, and his experiences with lawyer Ben Corbett, recounting one man's pursuit of justice in the face of the resurgence of Ku Klux Klan racism and violence in 1906 Eudora, Mississippi.
Keywords: Cross, Alex (Fictitious character) -- Fiction; African Americans -- Southern States -- Social conditions -- Fiction; Southern States -- Race relations -- Fiction; Legal stories